Genetic determination of heart and kidney weights studied using a set of recombinant inbred strains: the relationship to blood pressure - Kunes, J; Kren, V; Klír, P; Zicha, J; Pravenec, M (Journal of hypertension, 1990)
The effects of genetic factors and blood pressure levels on heart and kidney weights were estimated in a set of recombinant inbred (RI) strains obtained by crossing normotensive rat (BN.lx) and genetically hypertensive rat (SHR) progenitor strains. Renal or cardiac hypertrophy in several normotensive RI strains, together with low organ weights in some hypertensive strains, indicate that genetic factors play an important role in heart and kidney weight determination. In RI strains, there was a slight positive correlation between systolic blood pressure and relative heart weight, while relative kidney weight correlated negatively with blood pressure. Indeed, the analysis of the degree of genetic determination in RI strains revealed higher values for the relative kidney weight than for the relative heart weight. Blood pressure has a lower degree of genetic determination than both organs. Several polymorphic loci were found to be associated with organ weight determination. Thus, the analysis of organ weights in RI strains revealed the influence of primary genetic factors rather than secondary blood pressure effects.
Keywords: velikost orgánu; Analysis of Variance; Male; Organ Size; srdce; genetické inženýrství; potkani inbrední SHR; Kidney; mužské pohlaví; hypertrofie; genetické markery; Cardiomegaly; krysa rodu Rattus; Animals; krevní tlak; ženské pohlaví; analýza rozptylu; kardiomegalie; ledviny; zvířata; Rats; Blood Pressure; Rats, Inbred SHR; Hypertrophy; Female; Heart; Genetic Markers; Genetic Engineering